Hyperkalemia measurement between blood gas analyser and main laboratory biochemistry analyser - Mohd Helmie Ismail; Kamarul Aryffin Baharuddin; Mohd Azmi Suliman; Mohd Faiz Mohd Shukri; Siti Natrah Che Has; Lo, Zhen Zhen (Malaysian Medical Association, 2021)
Introduction: Potassium level is measured for patients with high risk of hyperkalemia in the emergency department (ED) using both blood gas analyser (BGA) and biochemistry analyser (BCA). The study was conducted to evaluate the correlation and agreement of potassium measurement between BGA and BCA.